The Legality of Passage of the Nuclear-Powered Submarines: Are Malaysia and Indonesia in Catch-22? - M. H. M. Rusli (Московский журнал международного права, 2023)
INTRODUCTION. Southeast Asia is home to some of the most important sea lines of communications (SLOCs) which are not only significant maritime conuits for merchant vessels, but military vessels of the superpower nations as well. While there have never been any casualties involving nuclear-powered submarines in this region, the fact remains that the number of such vessels traversing Southeast Asian SLOCs is predicted to rise in years to come.MATERIALS AND METHODS. This research is a result of analysis of international treaties applied to navigation of nuclear-powered submarines. Some of the materials used for preparing this paper include 1) the UN Convention on the Law of the Sea 1982; 2) AUKUS pact. The methodological basis of the research consists of traditional methods: general scientific methods (in this case, based on general principles of law) and specific methods.RESEARCH RESULTS. Other than China, Australia is another State within this region projected to own nuclear-powered submarines by 2040 through AUKUS. These developments have raised concerns among leaders of Southeast Asian nations, particularly Malaysia and Indonesia, the caretaker States of the Straits of Malacca and Singapore as well as the Indonesian archipelagic sea lanes. These maritime waterways are traversed by thousands of vessels each year, including nuclear-powered submarines belonging to nations already possessing them.DISCUSSION AND CONCLUSIONS. This article concludes by reiterating that international law should provide an equitable balance between navigational rights and protection of the marine environment particularly in sea lines of communications which are subjected to liberal navigational rights, in relation to nuclear-powered submarines.